Infant feeding practices in Viet Nam - Truong Si Anh; Ngo Thi Thai Hoe; John Knodel; Le Huong; Tran Thi Thanh Thuy (Asia-Pacific Population Journal, 1996)
Sustained efforts to promote healthful infant feeding practices are likely to be required to maintain and improve the Currently favourable situation.